Alterations in the levels of cytokines associated with Th17 cells in the plasma of Guillain-Barre syndrome patients - Mubarik , Bushra; Iqbal , Afifa; Mukhtar , Shahid; Tahir, Romeeza (Journal of the Pakistan Medical Association, 2026)
Objective: To compare the cytokines associated with T helper 17 cells between Guillain-Barre syndrome patients and healthy controls. Method: The cross-sectional, comparative study was conducted from March 2024 to February 2025 at the Department of Immunology, University of Health Sciences, Lahore, Pakistan, and comprised Guillain-Barre syndrome patients in group A and healthy controls in group B. Plasma concentrations of interleukin-6 IL-6, interleukin-17, interleukin-21, interleukin-22 and interleukin-23 in both the groups were quantified using enzyme-linked immunosorbent assay. Data was analysed using SPSS 24. Results: Of the 88 subjects, 44(50%) were in group A with mean age 41.6±11.8 years, while 44(50%) were in group B with mean age 39.3±12.4 years. Both the groups had 26(59%) male and 18(41%) female subjects. Serum interleukin-6, interleukin-17 and interleukin-22 levels were significantly higher in group A patients than group B controls (p<0.05). In contrast, reduced serum interleukin-23 levels were found in the group A compared to group B, but the difference was not significant (p>0.05). Correlation analysis among cytokine levels showed that serum interleukin-21 levels were correlated with interleukin-22 levels in group A patients. Interleukin-17 concentrations did not show any significant relationship with other cytokine levels (p>0.05). Interleukin-6 was negatively correlated with disease duration (p<0.05). No significant associations were found among cytokine levels, disease subtypes and severity (p>0.05). Conclusion: The activity of T helper 17 cytokines was significantly elevated in Guillain-Barre syndrome patients, underlining the contribution of T helper 17 cell cytokines in Guillain-Barre syndrome and implying that these cytokines can be targeted for therapeutic modulation of the immune response. Key Words: Guillain-Barré Syndrome, Th17, Cytokines, ELISA.